2022
DOI: 10.3390/jpm12050658
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Statins for Primary Prevention of Cardiovascular Disease in Low- and Medium-Risk Males: A Causal Inference Approach with Observational Data

Abstract: In this study, we analyzed the effectiveness of statin therapy for the primary prevention of cardiovascular disease (CVD) in low- and medium-risk patients. Using observational data, we estimated effectiveness by emulating a hypothetical randomized clinical trial comparing statin initiators with statin non-initiators. Two approaches were used to adjust for potential confounding factors: matching and inverse probability weighting in marginal structural models. The estimates of effectiveness were obtained by inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 20 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Finally, it is also possible that a lack of in-person consultations at the beginning of the COVID-19 pandemic may have caused patients to neglect their condition, with consequent negative health outcomes. In any case, further studies will be necessary to identify the underlying reasons, and to assess the validity of prescribing statins to low-risk patients who continuously show poor adherence, resulting in poor statin effectiveness ( Chaure-Pardos et al, 2022 ). For them, alternative non-pharmacological measures might be a more appropriate choice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is also possible that a lack of in-person consultations at the beginning of the COVID-19 pandemic may have caused patients to neglect their condition, with consequent negative health outcomes. In any case, further studies will be necessary to identify the underlying reasons, and to assess the validity of prescribing statins to low-risk patients who continuously show poor adherence, resulting in poor statin effectiveness ( Chaure-Pardos et al, 2022 ). For them, alternative non-pharmacological measures might be a more appropriate choice.…”
Section: Discussionmentioning
confidence: 99%
“…However, while statin efficacy in primary prevention of CVD has been well demonstrated in clinical trials, their effectiveness in clinical practice is less clear. This is in part because the desired clinical effects are only achievable if the patient adheres to the treatment plan ( Chaure-Pardos et al, 2022 ). Adherence to long-term therapies for chronic illnesses has been described as suboptimal ( Menditto et al, 2018 ), particularly in the case of statins for primary CVD prevention ( Ofori-Asenso et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…We retrieved 3133 unique records, of which 200 were included in the review (Figure 1). All reasons for excluding records after full-text review are given in eAppendix 6 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
“…Seventy studies (35%) reported in the title that the study aimed to emulate a target trial; 180 (90%) did so in the Methods section. Twenty studies (10%) reported the study was prospectively registered, 16 of these 20 (80%)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation